The completely chaotic Christmas of Lottie Brooks - Kirby, Katie; Kirby, Katie (London puffin books, 2024)
Lottie Brooks loves Christmas, there's presents, all the KitKat Chunkys you can eat and no school for two weeks! But this year, Christmas might be a bit more chaotic than usual. The whole Brooks family are visiting for the festive break (along with some surprise visitors), there's a secret Santa to organize, and the hammies won't stop attacking Gavin, the Elf on the Shelf! Will Lottie survive the festivites intact or will she have to hide in the fort of shame until it's all over?
English stories
Keywords: Children's stories; Christmas fiction; Diary fiction; Humorous fiction